A Gfet Nitrile Sensor Using A Graphene-binding Fusion Protein - Abubaker A. Mohamed; Hironaga Noguchi; Mirano Tsukiiwa; Chen Chen; Rachel S. Heath; Takumi Komikawa; Masayoshi Tanaka; Mina Okochi; Sam P. de Visser; Yuhei Hayamizu; Christopher F. Blanford; Muhammad Qadri Effendy Mubarak (John Wiley & Sons, Ltd, 2024)
Volume:32 Issue: 46